Cutaneous blastomycosis: a clue to a systemic disease Blastomicose cutânea: um sinal de doença sistêmica - Alex G Ortega-Loayza; Tuyet Nguyen (Sociedade Brasileira de Dermatologia, 2013)
A 55-year-old male presented with back pain and slightly tender annular plaques with central ulceration on his face. A skin biopsy revealed scattered yeast with broad based buds. A CT scan of the abdomen revealed a pathologic T12 fracture. Tissue obtained from the spine confirmed budding yeasts. The patient was diagnosed with disseminated blastomycosis. The patient was treated with amphotericin and itraconazole and completely recovered. Paciente do sexo masculino, com 55 anos de idade, compareceu ao ambulatório com dores na costa e placas anulares ligeiramente sensíveis, com ulceração central na face. Uma biópsia cutânea revelou levedura disseminada, com brotos de base larga. A tomografia computadorizada do abdômen revelou uma fratura patológica da T12. Amostra de tecido obtido da coluna vertebral confirmou levedura em fase de brotamento. O paciente foi diagnosticado com blastomicose disseminada. Após tratamento com anfotericina e itraconazol, o paciente teve recuperação completa.